Haidar Nashir : Pendidikan Muhammadiyah dalam Pengembangan Ilmu Pengetahuan Berbasis Nilai Keislaman - Dandi Pamungkas; Fina Aidah Soraya; Anas Indratanaya; Nasrulloh Nasrulloh; Astika Nurul Hidayah (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Muhammadiyah movement, which is one of the largest Islamic organisations besides Nahdlatul Ulama' in Indonesia, is known for its contribution in modernising the education system. The discussion in this article highlights the role of Muhammadiyah in developing education based on values derived from Islam from primary to tertiary levels. The modernisation includes curriculum, teaching methods, and management of educational institutions that are relevant to the demands of the times. The integration of Islamic values into the education system aims not only to improve academic knowledge but also to build students' character according to Islamic teachings and values. Through the concept of holistic education that includes intellectual, moral, and spiritual aspects, Muhammadiyah seeks to create a generation that is intelligent and has integrity. The article also highlights Haedar Nashir's thoughts on progressive Islamic education, which emphasises the importance of innovation and human resource development as well as technological development for the nation's progress.